2022
DOI: 10.1080/22221751.2022.2056523
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic influenza A (H1N1) virus causes abortive infection of primary human T cells

Abstract: Influenza A virus still represents a noticeable epidemic risk to international public health at present, despite the extensive use of vaccines and anti-viral drugs. In the fight against pathogens, the immune defence lines consisting of diverse lymphocytes are indispensable for humans. However, the role of virus infection of lymphocytes and subsequent abnormal immune cell death remains to be explored. Different T cell subpopulations have distinct characterizations and functions, and we reveal the high heterogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Third, differences regarding leucocyte and its subsets among patients with viral infection also reflect the variance in the severity or progression of disease. Consistent with our find, previous studies have reported an increased leucocyte count and reduced lymphocyte count in patients with severe viral infection compared to non-severe cases, where the underlying mechanism primarily involves imbalance of immune system, including excessive activation of immune cells, hyperinflammation, and direct effects of the virus on lymphocyte recruitment [ 34 36 ]. The most crucial change in the decreased lymphocytes induced by viral infection is the decline in CD3 + T cells, which are regarded as key players in adaptive immunoreaction against influenza infection due to the potent cytotoxic function in activated CD3 + 8 + T cells, the function of producing a series of cytokines and facilitating synthesis and secretion of antibodies in CD3 + 4 + T cells, etc.…”
Section: Discussionsupporting
confidence: 92%
“…Third, differences regarding leucocyte and its subsets among patients with viral infection also reflect the variance in the severity or progression of disease. Consistent with our find, previous studies have reported an increased leucocyte count and reduced lymphocyte count in patients with severe viral infection compared to non-severe cases, where the underlying mechanism primarily involves imbalance of immune system, including excessive activation of immune cells, hyperinflammation, and direct effects of the virus on lymphocyte recruitment [ 34 36 ]. The most crucial change in the decreased lymphocytes induced by viral infection is the decline in CD3 + T cells, which are regarded as key players in adaptive immunoreaction against influenza infection due to the potent cytotoxic function in activated CD3 + 8 + T cells, the function of producing a series of cytokines and facilitating synthesis and secretion of antibodies in CD3 + 4 + T cells, etc.…”
Section: Discussionsupporting
confidence: 92%
“…According to Jake Dunning et al, patients with the most severe illnesses also have a higher proportion of transcripts associated with neutrophils and fewer transcripts connected to IFN- γ [ 21 ]. Although multiple studies [ 22 , 23 ] have shown a correlation between lymphopenia and severe influenza, the mechanism by which the adaptive cellular immune response is inhibited in severe influenza remains largely unknown [ 24 26 ]. When the lungs get infected with influenza, neutrophils are among the first cells attracted there and perform a defensive function [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Divergent concepts regarding the ultimate role(s) of apoptosis during IAV infection have been raised mainly by studies examining cells other than leukocytes and using non-human models such as mice [ 31 ]. This may in part be due to the fact that IAV infection of human monocytes/macrophages and lymphocytes is abortive, with evidence of virus-directed protein synthesis, but without the release of free, infectious viral progeny [ 6 , 17 , 33 , 34 , 35 ]. The consequences of IAV-induced cell death would depend in a large part on the cells affected, such as respiratory epithelial cells or monocyte/macrophages and lymphocytes [ 36 ].…”
Section: Is Apoptosis In Response To Iav Defensive or Deleterious?mentioning
confidence: 99%